2018
DOI: 10.1002/cne.24392
|View full text |Cite
|
Sign up to set email alerts
|

Eye‐specific segregation and differential fasciculation of developing retinal ganglion cell axons in the mouse visual pathway

Abstract: Prior to forming and refining synaptic connections, axons of projection neurons navigate long distances to their targets. While much is known about guidance cues for axon navigation through intermediate choice points, whether and how axons are organized within tracts is less clear. Here we analyze the organization of retinal ganglion cell (RGC) axons in the developing mouse retinogeniculate pathway. RGC axons are organized by both eye-specificity and topography in the optic nerve and tract: ipsilateral RGC axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 55 publications
0
30
1
Order By: Relevance
“…We previously reported that ipsilateral RGCs are segregated by laterality within the optic tract (Sitko et al, ). Here, we confirmed the lateralization of ipsilateral RGCs in the optic tract by quantifying the distribution of zsGreen signal in the SERT‐Cre::zsGreen mouse across the mediolateral axis of the tract.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We previously reported that ipsilateral RGCs are segregated by laterality within the optic tract (Sitko et al, ). Here, we confirmed the lateralization of ipsilateral RGCs in the optic tract by quantifying the distribution of zsGreen signal in the SERT‐Cre::zsGreen mouse across the mediolateral axis of the tract.…”
Section: Resultsmentioning
confidence: 95%
“…Pre‐target axon organization, a common feature of axon tracts (e.g., Imai et al, ; Zhou et al, ), is likely mediated by intrinsic axon–axon interactions, which are important for axon targeting (Wang et al, ), and extrinsic factors, including cues from surrounding cells, such as glia in and around the tract. RGC axons in the developing mouse retinogeniculate pathway are organized by both topography (Chan & Chung, ) and laterality (i.e., ipsi‐ and contralateral axons; Godement, Salaun, & Imbert, ), and ipsilateral RGC axons self‐fasciculate more than contralateral axons in vitro (Sitko, Kuwajima, & Mason, ). However, other mechanisms mediating pre‐target axon order in the developing optic tract, in particular, the tendency of ipsilateral RGC axons to course in the lateral tract, remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…() after making lesions in the cat retina and silver staining to track degenerating axons. We gained more traction on the topic recently; with fluorescent dye‐ and genetic labeling we investigated eye‐specific organization of the mouse optic tract (Lee et al ., ; Sitko et al ., ).…”
Section: Time With Ray—launching My Journeymentioning
confidence: 97%
“…After mingling with each other in the optic chiasm, crossed and uncrossed fibers immediately segregate in the proximal optic tract (Sitko et al ., ). The molecular underpinnings of this segregation are beginning to emerge, and include dystroglycan (Clements & Wright, ), matrix molecules (Reese et al ., , ; Hornberg et al ., ), glial cells (Reese et al ., ; Lee et al ., ), and elements important for local translation of guidance proteins (Hornberg et al ., ), but a strict expression pattern associated with the ipsi‐ vs. contralateral RGC populations has not been established.…”
Section: Development Of the Ipsilateral And Contralateral Projection mentioning
confidence: 97%
See 1 more Smart Citation